A low surface energy self-sealing gradient radar absorbing coating and its use method
By using incompatible polymers and adhesives in radar absorbing coatings to form a gradient organic protective film, and combining highly weather-resistant and modified magnetic metal powders, the durability of radar absorbing coatings in corrosive environments is solved. The high weather resistance and excellent mechanical properties of single-layer coating are achieved.
Patent Information
- Application Number
- CN202310380802.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-04-11
AI Technical Summary
Existing radar absorbing coatings are prone to corrosion in humid, heat, high temperature or salt spray environments, resulting in deterioration of magnetic properties and reduced mechanical properties, and the multi-layer coating process increases cost and construction time.
Using low-surface energy self-sealing gradient radar absorbing coating, by selecting incompatible polymers and adhesives, the polymers are automatically enriched at room temperature to form a gradient organic protective film, and use high weather resistance modification on the surface. Magnetic metal powders, combined with specific mixed solvents and diluents, form dual weather resistance and excellent mechanical properties.
Long-term corrosion protection and excellent mechanical properties after single layer coating are achieved, reducing construction cycle and cost, while avoiding the problem of weak interlayer bonding force, improving production efficiency and weather resistance.
Smart Images

Figure CN116355448B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of radar absorbing coating corrosion protection, and specifically relates to a low surface energy self-sealing gradient radar absorbing coating and a use method thereof, which can be applied to a strong corrosive environment. Background Art
[0002] Radar absorbing coatings, as a material for controlling electromagnetic radiation, are often used in the fields of aviation, aerospace, and consumer electronics. In order to achieve effective control of electromagnetic radiation, it is often necessary to add a large amount of magnetic metal powders to the coating system, such as carbonyl iron powder, carbonyl nickel powder, ferrite and other functional powders. However, due to the relatively active nature of these materials, they are very susceptible to corrosion in humid, hot, or salty environments, causing a significant deterioration in their magnetic properties, resulting in a significant reduction in the control of electromagnetic radiation by radar absorbing coatings and a significant deterioration in their mechanical properties, thus limiting the scope of application of these materials.
[0003] At present, there are two technical approaches commonly used in the industry to improve the weather resistance of radar absorbing coatings.
[0004] The first technical approach is to coat and modify the magnetic metal powder by surface modification technology. This method inhibits corrosive media such as chloride ions, sodium ions, sulfate ions, water, and oxygen from contacting the magnetic metal powder by coating a layer of inorganic or organic material on the surface of the magnetic metal powder, thereby improving the corrosion resistance of the coating. For example: Patent CN112563010A forms a 10-100nm silica coating layer on the surface of carbonyl iron powder. The functional coating test piece prepared by this method can achieve no rust on the surface after 1000-1500 hours of salt spray corrosion test. CN113105811A uses alloy magnetic powder and carbon-based absorber to prepare corrosion-resistant lightweight broadband absorbing coating, which does not corrode in neutral salt spray for 2400 hours or acidic salt spray for 300 hours. For example, patent ZL.202210215327.5 provides a method for preparing highly weather-resistant resin-coated magnetic metal powder, and the absorbing coating prepared by the method can withstand neutral salt spray for more than 3000 hours. However, most single-layer radar absorbing coatings cannot achieve durability in corrosive environments.
[0005] The second technical approach is to apply a layer of corrosion protection topcoat on the surface of the radar absorbing coating. However, the application of multiple layers of coating increases the construction process, takes a long time and is costly. At the same time, there are differences in surface energy between layers, resulting in weak interlayer bonding. For example, patent CN110684438B discloses a water-based anti-corrosion and aging-resistant absorbing coating and a preparation method thereof. The method adopts a three-layer system of epoxy primer layer, polyurethane absorbing layer and polyurethane topcoat layer to address the problem of poor corrosion resistance of the absorbing coating. Patent CN107892871B discloses an anti-corrosion absorbing coating and a preparation method thereof. The method also adopts a three-layer system of acrylic polyurethane base layer, absorbing layer and anti-corrosion surface layer. However, the three-layer corrosion protection system significantly increases the construction process, prolongs the manufacturing time and increases the cost. Summary of the invention
[0006] In view of the above-mentioned problems or shortcomings, and in order to solve the problems of poor durability or process cost of the existing radar absorbing coating corrosion resistance technology, the present invention provides a low surface energy self-sealing gradient radar absorbing coating and a method of using the same. The radar absorbing coating prepared by the present invention not only has long-term corrosion protection characteristics and excellent mechanical properties, but also avoids the disadvantage of weak interlayer bonding after the corrosion protection topcoat is applied on the surface of the radar absorbing coating, thereby reducing the construction process cycle and raw material costs.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A low surface energy self-sealing gradient radar absorbing coating comprises, by mass fraction, 15 to 25 parts of a resin binder, 45 to 75 parts of a mixed solvent, 3 to 5 parts of a polymer, 0.75 to 1.25 parts of an auxiliary agent 1, 0.45 to 0.75 parts of an auxiliary agent 2, 1.2 to 2.4 parts of an auxiliary agent 3, 150 to 300 parts of magnetic metal powder, 15 to 25 parts of a curing agent, and 35 to 120 parts of a diluent.
[0009] The resin adhesive is polyurethane resin, epoxy resin or acrylic resin; the first auxiliary agent is a fumed silica anti-settling agent; the second auxiliary agent is an acrylic ester leveling agent; the third auxiliary agent is a silane coupling agent; the curing agent is an aliphatic amine curing agent; and the diluent is three or four of butyl ether, butanone, ethyl ester and butyl ester.
[0010] The polymer is two or three of 2,4-dichlorobenzoyl peroxide, dicumyl peroxide and trimethylolpropane trimethacrylate.
[0011] The mixed solvent is two or three of butyl ester, xylene, butanone and ethyl ester. The mixed solvent is used to dissolve the resin binder and the polymer on the one hand, and to reduce the volatilization rate and improve the efficiency of the gradient distribution of the coating on the other hand.
[0012] Furthermore, the magnetic metal powder is a magnetic metal powder with a highly weather-resistant surface modification, such as a magnetic metal powder coated with a highly weather-resistant resin, so that the final radar absorbing coating has a double improvement in weather resistance.
[0013] The method for using the low surface energy self-sealing gradient radar absorbing coating comprises the following steps:
[0014] Step 1: Dissolve the resin binder in a mixed solvent at room temperature to obtain a mixed solution A.
[0015] Step 2: Disperse the polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B.
[0016] Step 3: Add the magnetic metal powder to the mixed solution B obtained in step 2, and mix them to obtain a pre-dispersed material C.
[0017] Step 4: Add the additive 1, additive 2 and additive 3 to the pre-dispersed material C obtained in step 3, and mix them to obtain a mixed solution D.
[0018] Step 5: Evenly mix the mixed liquid D with the curing agent and the diluent to obtain a low surface energy self-sealing gradient radar absorbing coating.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. There is incompatibility between the polymer selected in the present invention and the adhesive. Under room temperature curing conditions, the polymer will automatically and gradually enrich from the inside of the coating to the surface. The selection of two or three polymer materials will form a gradient organic protective film due to the different types of materials, thereby forming a low surface energy self-sealing gradient radar absorbing coating.
[0021] 2. The low surface energy self-sealing gradient radar absorbing coating designed by the present invention can further accumulate weather resistance by using the existing magnetic metal powder with high weather resistance modification on the surface, and the gradient organic protective film from the inside to the surface of the coating enriched with several polymers provides the radar absorbing coating with long-term weather resistance and excellent mechanical properties; at the same time, the gradient organic protective film layer further reduces the surface energy of the coating and has excellent hydrophobic properties.
[0022] 3. The process of the present invention is simple and mature, with strong operability and is suitable for large-scale production. Compared with the same type of radar absorbing coatings, the self-sealing gradient characteristics of the present invention avoid the use of anti-corrosion topcoat and the disadvantage of weak interlayer bonding caused by multiple coatings, shorten the construction period, improve production efficiency and reduce the use cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1SEM image of the cross section of the self-sealing gradient radar absorbing coating prepared in Example 1;
[0024] Figure 2 Surface energy (contact angle) test results of the self-sealing gradient radar absorbing coating prepared in Example 1;
[0025] Figure 3 Tafel curve diagram of Example 1 and control group;
[0026] Figure 4 SEM image of the cross section of the self-sealing gradient radar absorbing coating prepared in Example 2;
[0027] Figure 5 Surface energy (contact angle) test results of the self-sealing gradient radar absorbing coating prepared in Example 2;
[0028] Figure 6 Tafel curve diagram of Example 2 and control group;
[0029] Figure 7 SEM image of the cross section of the self-sealing gradient radar absorbing coating prepared in Example 3;
[0030] Figure 8 Surface energy (contact angle) test results of the self-sealing gradient radar absorbing coating prepared in Example 3;
[0031] Fig. 9 Tafel curve diagram of Example 3 and control group;
[0032] Fig.10 SEM image of the cross section of the self-sealing gradient radar absorbing coating prepared in Example 4;
[0033] Fig.11 Surface energy (contact angle) test results of the self-sealing gradient radar absorbing coating prepared in Example 4;
[0034] Fig.12 Tafel plot of Example 4 and the control group. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, control groups and drawings.
[0036] The control group uses the radar absorbing coating prepared in CN202210215327.5 for comparison with the embodiments of the present invention.
[0037] Example 1
[0038] Step 1: Dissolve 15 parts of polyurethane resin in 45 parts of a mixed solvent at room temperature to obtain a mixed solution A, wherein the mixed solvent is butyl ester, xylene and butanone in a mass ratio of 4:3:2.
[0039] Step 2: Disperse 3 parts of a polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B, wherein the polymer is 2,4-dichlorobenzoyl peroxide and trimethylolpropane trimethacrylate in a mass ratio of 2:1.
[0040] Step 3: Add 150 parts of high weather-resistant resin-coated magnetic metal powder (modified powder) to the mixed solution B obtained in step 2, and stir thoroughly to obtain a uniformly mixed pre-dispersed material C.
[0041] Step 4: Add 0.75 parts of auxiliary agent 1, 0.45 parts of auxiliary agent 2 and 1.2 parts of auxiliary agent 3 to the pre-dispersed material C obtained in step 3, and stir evenly to obtain a mixed solution D. The ratio of the mixed solvent is the same as that in step 1.
[0042] Step 5: Evenly mix the mixed solution D obtained in step 4 with 15 parts of curing agent and 35 parts of diluent to obtain a low surface energy self-sealing gradient radar absorbing coating. The diluent is butyl ether, butanone and ethyl ester in a mass ratio of 4:1:2.
[0043] Figure 1 This is a cross-sectional SEM image of the low surface energy self-sealing gradient radar absorbing coating prepared in Example 1. Figure 2 The surface energy test results of the radar absorbing coating prepared in Example 1 are as follows: Figure 3 1 is a Tafel curve diagram of Example 1 and a control group. Table 1 is a comparison result of corrosion parameters of the radar absorbing coating prepared in Example 1 and the control group.
[0044] An organic protective film layer was successfully formed on the surface of the low surface energy self-sealing gradient radar absorbing coating prepared in Example 1, with a contact angle of 119.97°, an adhesion of 29.5 MPa, and a flexibility of 5 mm. The electrode potential of the radar absorbing coating prepared in Example 1 was increased to 0.090 V, and the corrosion current density was increased by 2 orders of magnitude. The low surface energy self-sealing gradient radar absorbing coating prepared in Example 1 has a neutral salt spray resistance time of more than 8064 hours and an acid salt spray resistance (PH = 3.5) of more than 5040 hours without corrosion.
[0045] Table 1: Corrosion parameter changes of Example 1 and the control group
[0046] parameter Electrode potential Corrosion current density Control group -0.009V <![CDATA[6.14×10 -8 A / cm 2 ]]> Example 1 0.090V <![CDATA[3.21×10 -10 A / cm 2 ]]>
[0047] Example 2
[0048] Step 1: Under room temperature, 20 parts of epoxy resin are dissolved in 60 parts of a mixed solvent to obtain a mixed solution A, wherein the mixed solvent is xylene, butanone and ethyl acetate in a mass ratio of 4:1:1.
[0049] Step 2, dispersing 4 parts of the polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B, wherein the polymer is 2,4-dichlorobenzoyl peroxide, diisopropylbenzene peroxide and trimethylolpropane trimethacrylate in a mass ratio of 2:1:1;
[0050] Step 3: Add 200 parts of high weather-resistant resin-coated magnetic metal powder (modified powder) to the mixed solution B obtained in step 2, and stir thoroughly to obtain a uniformly mixed pre-dispersed material C.
[0051] Step 4: Add 1 part of auxiliary agent 1, 0.6 parts of auxiliary agent 2 and 1.8 parts of auxiliary agent 3 to the pre-dispersed material C obtained in step 3, and stir evenly to obtain a mixed solution D. The ratio of the mixed solvent is the same as that in step 1.
[0052] Step 5: Evenly mix the mixed solution D obtained in step 4 with 18 parts of curing agent and 42 parts of diluent to obtain the self-sealing gradient radar absorbing coating. The diluent is butyl ether, butanone, ethyl ester and butyl ester, and the mass ratio thereof is 10:6:4:1.
[0053] Figure 4 This is a cross-sectional SEM image of the low surface energy self-sealing gradient radar absorbing coating prepared in Example 2. Figure 5 The surface energy test results of the radar absorbing coating prepared in Example 2 are as follows: Figure 6 2 is a Tafel curve diagram of Example 2 and the control group. Table 2 is a comparison result of corrosion parameters between the radar absorbing coating prepared in Example 2 and the control group.
[0054] An organic protective film layer was successfully formed on the surface of the radar absorbing coating prepared in Example 2, with a contact angle of 122.84°, an adhesion of 30.1 MPa, and a flexibility reduced to 5 mm. The electrode potential of the radar absorbing coating prepared in Example 2 was increased to 0.098 V, and the corrosion current density was increased by 2 orders of magnitude. The radar absorbing coating prepared in Example 2 had a neutral salt spray resistance of more than 8160 hours and an acid salt spray resistance (PH = 3.5) of more than 5280 hours without corrosion.
[0055] Table 2: Corrosion parameter changes of Example 2 and the control group
[0056]
[0057]
[0058] Example 3
[0059] Step 1: Under room temperature, 23 parts of acrylic resin are dissolved in 70 parts of a mixed solvent to obtain a mixed solution A, wherein the mixed solvent is xylene and ethyl acetate in a mass ratio of 5:3.
[0060] Step 2: Disperse 4.5 parts of a polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B, wherein the polymer is dicumyl peroxide and trimethylolpropane trimethacrylate in a mass ratio of 3.5:1.
[0061] Step 3: Add 240 parts of high weather-resistant resin-coated magnetic metal powder (modified powder) to the mixed solution B obtained in step 2, and stir thoroughly to obtain a uniformly mixed pre-dispersed material C.
[0062] Step 4: Add 1 part of auxiliary agent 1, 0.6 parts of auxiliary agent 2 and 1.8 parts of auxiliary agent 3 to the pre-dispersed material C obtained in step 3, and stir evenly to obtain a mixed solution D. The type and proportion of the mixed solvent are the same as those in step 1.
[0063] Step 5: Evenly mix the mixed solution D obtained in step 4 with 23 parts of curing agent and 80 parts of diluent to obtain a low surface energy self-sealing gradient radar absorbing coating. The diluent is butyl ether, butanone, ethyl ester and butyl ester in a mass ratio of 5:3:2:2.
[0064] Figure 7 This is a cross-sectional SEM image of the low surface energy self-sealing gradient radar absorbing coating prepared in Example 3. Figure 8 The surface energy test results of the radar absorbing coating prepared in Example 3 are as follows: Fig. 9 3 is a Tafel curve diagram of Example 3 and the control group. Table 3 is a comparison result of corrosion parameters of the radar absorbing coating prepared in Example 3 and the control group.
[0065] The radar absorbing coating prepared in Example 3 successfully formed an organic protective film layer on its surface, with a contact angle of 119.43°, an adhesion of 31.3MPa, and a flexibility of 5mm. The electrode potential of the radar absorbing coating prepared in Example 3 was increased to 0.086V, and the corrosion current density was increased by 2 orders of magnitude. The radar absorbing coating prepared in Example 3 has a neutral salt spray resistance of more than 8160 hours and an acid salt spray resistance (PH=3.5) of more than 5184 hours without corrosion.
[0066] Table 3: Corrosion parameter changes of Example 3 and the control group
[0067] parameter Electrode potential Corrosion current density Control group -0.009V <![CDATA[6.14×10 -8 A / cm 2 ]]> Example 3 0.086V <![CDATA[3.11×10 -10 A / cm 2 ]]>
[0068] Example 4
[0069] Step 1: Under room temperature, 25 parts of epoxy resin are dissolved in 75 parts of a mixed solvent to obtain a mixed solution A, wherein the mixed solvent is xylene and ethyl acetate in a mass ratio of 5:3.
[0070] Step 2: Disperse 5 parts of a polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B, wherein the polymer is 2,4-dichlorobenzoyl peroxide and trimethylolpropane trimethacrylate in a mass ratio of 3:2.
[0071] Step 3: Add 300 parts of high weather-resistant resin-coated magnetic metal powder (modified powder) to the mixed solution B obtained in step 2, and stir thoroughly to obtain a uniformly mixed pre-dispersed material C.
[0072] Step 4: Add 1.25 parts of auxiliary agent 1, 0.75 parts of auxiliary agent 2 and 2.4 parts of auxiliary agent 3 to the pre-dispersed material C obtained in step 3, and stir evenly to obtain a mixed solution D. The type and proportion of the mixed solvent are the same as those in step 1.
[0073] Step 5: Evenly mix the mixed solution D obtained in step 4 with 25 parts of curing agent and 120 parts of diluent to obtain a low surface energy self-sealing gradient radar absorbing coating. The diluent is butyl ether, ethyl ester and butyl ester in a mass ratio of 5:2:1.
[0074] Fig.10 This is a cross-sectional SEM image of the low surface energy self-sealing gradient radar absorbing coating prepared in Example 4. Fig.11 The surface energy test results of the radar absorbing coating prepared in Example 4 are as follows: Fig.12 3 is a Tafel curve diagram of Example 4 and the control group. Table 3 is a comparison result of corrosion parameters of the radar absorbing coating prepared in Example 4 and the control group.
[0075] An organic protective film was successfully formed on the surface of the radar absorbing coating prepared in Example 4, with a contact angle of 124.45°, an adhesion of 30.4 MPa, and a flexibility of 5 mm. The electrode potential of the radar absorbing coating prepared in Example 4 was increased to 0.102 V, and the corrosion current density was increased by 2 orders of magnitude. The radar absorbing coating prepared in Example 4 had a neutral salt spray resistance of more than 8064 hours and an acid salt spray resistance (PH = 3.5) of more than 5184 hours without corrosion.
[0076] Table 4: Corrosion parameter changes of Example 4 and the control group
[0077] parameter Electrode potential Corrosion current density Control group -0.009V <![CDATA[6.14×10 -8 A / cm 2 ]]> Case 4 0.102V <![CDATA[1.32×10 -10 A / cm 2 ]]>
[0078] It can be seen from the above embodiments and comparative examples that the present invention adopts the modified metal powder in ZL.202210215327.5, selects incompatible polymers and adhesives, and selects two to three materials for the polymer. Due to the different types of materials, the polymer will automatically enrich from the inside of the coating to the surface under room temperature curing conditions to form a gradient organic protective film, and finally form a low surface energy self-sealing gradient radar absorbing coating. At the same time, the gradient organic protective film layer further reduces the surface energy of the coating and has excellent hydrophobic properties. The process of the present invention is simple and mature, with strong operability, and avoids the use of anti-corrosion topcoat, avoids the disadvantages of weak interlayer bonding caused by multiple brushing, reduces the construction period, improves production efficiency, and reduces the cost of use. The prepared radar absorbing coating has the advantages of long corrosion resistance time, excellent mechanical properties, and low cost after single-layer coating.
Claims
1. A low surface energy self-sealing gradient radar absorbing coating, characterized in that: The composition comprises, by weight: 15 to 25 parts of resin binder, 45 to 75 parts of mixed solvent, 3 to 5 parts of polymer, 0.75 to 1.25 parts of auxiliary agent 1, 0.45 to 0.75 parts of auxiliary agent 2, 1.2 to 2.4 parts of auxiliary agent 3, 150 to 300 parts of magnetic metal powder, 15 to 25 parts of curing agent, and 35 to 120 parts of diluent; The resin adhesive is polyurethane resin, epoxy resin or acrylic resin; the first auxiliary agent is a fumed silica anti-settling agent; the second auxiliary agent is an acrylic ester leveling agent; the third auxiliary agent is a silane coupling agent; the curing agent is an aliphatic amine curing agent; the diluent is three or four of butyl ether, butanone, ethyl ester and butyl ester; The polymer is 2,4-dichlorobenzoyl peroxide and trimethylolpropane trimethacrylate, diisopropylbenzene peroxide and trimethylolpropane trimethacrylate, and 2,4-dichlorobenzoyl peroxide, diisopropylbenzene peroxide and trimethylolpropane trimethacrylate, a total of three combinations; The mixed solvent is two or three of butyl ester, xylene, butanone and ethyl ester; the mixed solvent dissolves the resin adhesive and the polymer on the one hand, and reduces the volatilization rate on the other hand, thereby improving the efficiency of forming a gradient distribution of the coating.
2. The low surface energy self-sealing gradient radar absorbing coating according to claim 1, characterized in that: The magnetic metal powder is a magnetic metal powder with a highly weather-resistant surface modification, so that the final radar absorbing coating has a double improvement in weather resistance.
3. The method for using the low surface energy self-sealing gradient radar absorbing coating as claimed in claim 1 comprises the following steps: Step 1, dissolving a resin binder in a mixed solvent at room temperature to obtain a mixed solution A; Step 2, dispersing the polymer in the mixed solution A obtained in step 1 to obtain a mixed solution B; Step 3, adding the magnetic metal powder to the mixed solution B obtained in step 2, and mixing them to obtain a pre-dispersed material C; Step 4, adding the additive 1, additive 2 and additive 3 to the pre-dispersed material C obtained in step 3, and mixing to obtain a mixed solution D; Step 5: Evenly mix the mixed liquid D with the curing agent and the diluent to obtain a low surface energy self-sealing gradient radar absorbing coating.
